A Comparative Analysis of the Mechanical Properties of Annealed PLA - Zisopol, D. G.; Portoaca, A. I.; Nae, I.; Ramadan, I. (Engineering, Technology & Applied Science Research, 2022)
In order to obtain better performance, 3D printed parts can be the subject of post-processing operations like sanding, gap filling, polishing, annealing, epoxy coating, and metal plating. This paper takes into consideration the most commonly used material filament for FFF technology PLA and studies the mechanical characteristics through tensile and 3-point bending tests. The obtained results reveal significantly higher values of the mechanical properties after applying a 3-hour heat treatment at 75°C, for the following combinations of parameters: layer thickness of 0.10, 0.15, and 0.20mm and infill percentage of 50%, 75%, and 100%.